Bending resistance of stainless steel beams at elevated temperatures - Alves, Matheus Henrique (2021)
To analyse the structural behaviour of stainless steel members at elevated temperatures, a set of three-point bending tests on RHS 150x100x5 beams of the grade 1.4301 were conducted. Numerical modelling of these tests has been afterwards performed at the measured temperatures, achieving close approximation to observed experimental results. Analytical methods to predict the load-deflection behaviour are also analysed.